Faktor-faktor yang Menyebabkan Hipotensi Intradialisis : Literature Review - Muhammad Nur Sidiq (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Chronic kidney disease is a progressive and irreversible disorder of kidney function where the body experiences fail to maintain metabolism, fluid and electrolyte balance, and causing uremia. Hemodialysis is done to eliminate the symptoms, namely controlling uremia, excess fluid and electrolyte imbalances that occur in patients with chronic kidney disease. In addition to the benefits of hemodialysis, it is also have many of complications, one of the most common complications is intradialysis hypotension (IDH), cases of intradialysis hypotension reach 20% to 30% in the hemodialysis session. The method used is a literature review study by comparing some literature from search sites accredited journals such as Scientdirect, the National Center for Biotechnology Information and Google Scholar with the keywords Hypotension Intradyalitic Factor in the period 2015-2020. Research result :. Intradialysis hypotension (IDH) occurs due to mulifactorial both non-technical factors and hemodialysis technical factors. Non-technical factors consist of gender, age, history of hypertension, heart disease, anemia and patient's hemodialysis duration. Technical factors consist of ultrafiltration rate, dialysate liquid temperature, and dialysate fluid concentration. Conclusion: Intradialysis hypotension occurs because it is preceded by mulftifactorial factors, IDH occurs due to reduced aggressive blood circulation volume during the hemodialysis session